Crouching tiger, hidden dragon - Lee, Ang, 1954-; Chow, Yun-fat.; Yeoh, Michelle, 1963-; Zhang, Ziyi, 1979-; Wang, Huiling, 1964-; Schamus, James, 1959-; Cai, Guorong; Kong, Bill.; Hsu, Li-kong.; Wang, Dulu.; Sony Pictures Classics (Firm); Columbia Pictures (Culver City, Calif. : Columbia Pictures, 2001)
"Two master warriors (Chow Yun Fat and Michelle Yeoh) are faced with their greatest challenge when the treasured Green Destiny sword is stolen. A young aristocrat (Zhang Ziyi) prepares for an arranged marriage, but soon reveals her superior fighting talents and her deeply romantic past. As each warrior battles for justice, they come face to face with their worst enemy - and the inescapable, enduring power of love. Set against 19th Century China's breathtaking landscape, Crouching Tiger, Hidden Dragon is the action-packed, box office smash from acclaimed director Ang Lee (Sense and Sensibility, The Ice Storm) featuring stunning martial arts choreography by Yuen Wo Ping (The Matrix)."-- Container.
Based on the book by Wang Du Lu.
Credits: music composed by, Tad Dun ; cello solos by, Yo-Yo Ma ; edited by, Tim squyres ; action choreographed by, Yuen Wo Ping ; photographed by, Peter Pau ; directed by Ang Lee ; screenplay by Wang Hui Ling, James Schamus and Tsai Kuo-jung ; produced by Bill Kong, Hsu Li Kong, Ang Lee..
Casts: Chow Yun Fat, Michelle Yeoh, Zhang Zi Yi.
Rating: PG-13.
Color recording system: NTSC.
DVD ; region 1 ; dolby digital.
Keywords: Women martial artists -- China -- Drama; Martial artists -- China -- Drama; Swords -- China -- Drama; Feature films